Estimating psychological impact of unemployment: The case of Malaysian graduates - Lim, Hock-eam (Malaysian journal of economic studies, 2010)
The objective of this paper is to estimate the psychological impact of unemployment for a group of 240 Malaysian graduates during their transition from university to labour market. There is evidence of negative psychological impact of unemployment. Results also reveal that treating employment or unemployment as a homogenous state is subject to state aggregation bias. [PUBLICATION ABSTRACT]